Horror noire [videorecording (DVD)] : a history of Black horror - Cundieff, Rusty; Dickerson, Ernest R., 1952-; Peele, Jordan, 1979-; True, Rachel; David, Keith; Todd, Tony, 1952-; Due, Tananarive, 1966-; Means Coleman, Robin R., 1969-; Means Coleman, Robin R., 1969- (Image Entertainment, 2021)
Delving into a century of genre films that by turns utilized, caricatured, exploited, sidelined, and finally embraced them, this documentary traces the untold history of Black Americans in Hollywood through their connection to the horror genre. Adapting Robin Means Coleman's seminal book, this will present the living and the dead, using new and archival interviews from scholars and creators; the voices who survived the genre's past trends, to those shaping its future.